2021
DOI: 10.5114/cipp.2021.104800
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Parental Responsiveness Scale

Abstract: Parental responsiveness is a parent's predisposition to react to their child's verbal and non-verbal cues promptly and adequately. There is no self-report scale that measures this type of behavior. The aim of this study was to construct a valid and useful scale to measure this construct as subjectively reported by parents of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This brings to mind the observation that parental responsiveness is a type of behavior strongly embedded in situational context. The threatening situation of the pandemic might lead to subjectively perceived higher parental involvement and attentiveness in responding to the child’s signals and reacting to them more promptly and adequately [ 27 ]. Moreover, our previous studies showed that parental responsiveness is linked to greater empathic concern and perspective taking [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This brings to mind the observation that parental responsiveness is a type of behavior strongly embedded in situational context. The threatening situation of the pandemic might lead to subjectively perceived higher parental involvement and attentiveness in responding to the child’s signals and reacting to them more promptly and adequately [ 27 ]. Moreover, our previous studies showed that parental responsiveness is linked to greater empathic concern and perspective taking [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parental responsiveness was measured by the Parental Responsiveness Scale [ 27 ]. It consists of 13 statements that pertain to parental sensitive responsiveness towards young children (up to 2 years).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations